Clinicopathologic Characteristics of Renal Cell Carcinoma in Prof. dr. I.G.N.G. Ngoerah General Hospital 2018 – 2022 (Research, Society and Development, 2023)
RCC is a tumor that manifests in proximal tubule epithelial cells and accounts for 3% of total adult neoplastic cases. In Indonesia, RCC cases are still deemed low, but show a tendency to increase annually. This study’s objective is to provide a description on the clinicopathologic features of RCC patients in Prof. dr. I.G.N.G. Ngoerah General Hospital in the province of Bali from 2018 to 2022. This is a cross-sectional study which implemented total sampling in collecting secondary data from the laboratory of anatomical pathology in Prof. dr. I.G.N.G. Ngoerah General Hospital. There were 38 cases of RCC from a total of 108 kidney cases which underwent histopathologic examinations. Descriptive analysis showed that the majority of RCC cases were found in the age range of 51 – 60 years old (36.8%), males (76,3%), left tumor laterality (57,9%), operative procedures for specimen collection (94,7%), ccRCC subtype (63,2%), tumor size of >10 cm (50,0%), grade III – IV (57,9%), and pT3a stage (47,4%). The combination of these clinicopathologic findings suggested that the RCC patients in Bali were shown to be associated with worse prognosis and should consider further analytical studies.